Unsteady laminar mixed convection boundary layer flow near a vertical wedge due to oscillations in the free-stream and surface temperature - Roy, Nepal Chandra; Hossain, Md. Anwar; Hussain, Sharmina (© 2016 De Gruyter Open Ltd., 2016)
This article was published in the International Journal of Applied Mechanics and Engineering [© 2016 International Journal of Applied Mechanics and Engineering] and the definite version is available at : http://doi.org/10.1515/ijame-2016-0011. The Journal's website is at: https://www.degruyter.com/view/j/ijame.2016.21.issue-1/ijame-2016-0011/ijame-2016-0011.xml